170k views
1 vote
Solve the following linear system of equations using substitution.

y = 3x – 5
y = 2x – 6

(3, 2)

(–5, –6)

(–1, –8)

(1, –2)

User Jon
by
5.0k points

2 Answers

2 votes

Answer:

( - 1, - 8 )

Explanation:

just took it on edge

User Roman Vottner
by
5.3k points
2 votes

( - 1, - 8 )

since both equations give y in terms of x we can equate them

3x - 5 = 2x - 6

subtract 2x from both sides of the equation

3x - 2x - 5 = - 6

x - 5 = - 6

add 5 to both sides

x = - 6 + 5 = - 1

substitute x = - 1 into either of the 2 equations for y

y = (3 × - 1) - 5 = - 3 - 5 = - 8

solution to the system is (- 1, - 8 )



User Benjy Wiener
by
5.7k points